2018
DOI: 10.15640/ijgws.v6n2a9
|View full text |Cite
|
Sign up to set email alerts
|

Housework and Couple Satisfaction: Satisfaction with Housework Division and Gender Ideology among Italian Dual-Earner Couples

Abstract: This article reports on a study that examined the division of housework in 105 Italian dual-earner couples and the relationships between this division, the participants' satisfaction with it, gender ideology, and couple satisfaction. The findings show that women devoted much more time to housework than men, performed a greater number of routine female tasks, and reported lower levels of satisfaction with housework arrangements. However, women and men did not differ in levels of couple satisfaction. Satisfactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…However, children’s gender has been found to be an important predictor of marital stability and marital satisfaction (Kabátek & Ribar, 2021; Raley & Bianchi, 2006; W. H. Yu & Kuo, 2018), which are two of the most important predictors of housework division between husbands and wives (Antonelli, 2018; Baxter et al, 2008; Carlson et al, 2020). These empirical studies revealed a potential link between children’s gender and the parents’ division of housework, which is consistent with the theoretical link established in the above discussion.…”
mentioning
confidence: 99%
“…However, children’s gender has been found to be an important predictor of marital stability and marital satisfaction (Kabátek & Ribar, 2021; Raley & Bianchi, 2006; W. H. Yu & Kuo, 2018), which are two of the most important predictors of housework division between husbands and wives (Antonelli, 2018; Baxter et al, 2008; Carlson et al, 2020). These empirical studies revealed a potential link between children’s gender and the parents’ division of housework, which is consistent with the theoretical link established in the above discussion.…”
mentioning
confidence: 99%